APLIKASI PENCARIAN WARUNG MAKAN KHAS MINANG (NASI PADANG) TERDEKAT DI KOTA SEMARANG MENGGUNAKAN LBS (LOCATION BASED SERVISE) BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract :As technology advances and information that has now grown by leaps and bounds , like a human life is not separate between distance , place , and time . People can easily communicate and access information no matter where he place. Moreover, the diversity of means of communication that is now circulating in the community , one of which is the android smartphone. The problem faced is how to build an application on the Android platform to search nasi padang restaurant locations and their addresses , as well as equipped with dialer. It has been answered with the android operating system is open source , so users are free to develop applications as they want , as well as point Typical Application Search Minang ( Nasi Padang ) , which has a feature point in the search for Eat Distinctive Minang ( nasi Padang ) in particular in the city of Semarang. With point Typical Application Search Minang ( Nasi Padang ) then users who have high mobility no longer need to search for the location of food stalls typical Minang ( Nasi Padang ) by searching or asking where the location of food stalls typical Minang ( NasiPadang ) nearby , because the point Application Search typical Minang ( Nasi Padang ) has been providing a complete search feature , so users especially in the city of Semarang can find the location of food stalls typical Minang ( Nasi Padang ) nearby whenever only with Android phones and point typical Application Search Minang ( Nasi Padang ) . This application can be used to help find the location of Public Eating and Distinctive Minang based districts closest location of the position we are . Thisapplication will display a Public Eating datail shop name, address , phone number , picture / photo shop and display maps are sourced from Google Maps Keywords: (Location Base Service), Android, Google Map’s, GPS.